The initiation of sound change : perception, production, and social factors - Solé, Maria-Josep; Recasens i Vives, Daniel, 1954- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2012)
The origins of sound change is one of the oldest and most challenging questions in the study of language. The goal of this volume is to examine current approaches to sound change from a variety of theoretical and methodological perspectives, including articulatory variation and modeling, speech perception mechanisms and neurobiological processes, geographical and social variation, and diachronic phonology. This diversity of perspectives contributes to a fruitful cross-fertilization across disciplines and represents an attempt to formulate converging ideas on the factors that lead to sound chan.